Penyelesaian Sengketa Akad Pembiayaan Murabahah Menurut Hukum Ekonomi Syariah (Analisis Putusan Pengadilan Agama Mataram Nomor 0508/PDT.G/2016/PA.MTR - Mohammad Hosen (Jurnal Justisia Ekonomika: Magister Hukum Ekonomi Syariah, 2019)
This research discusses the Decision of the Mataram Religious Court Number 0508/Pdt.G/2016/PA. Mtr on how the judges resolved the issue of the dispute over the murabahah financing contract in the Mataram Religious Court. In analyzing the problem the author uses the theories of Islamic Economic Law as the basis of the analysis. the main issues that will be answered through this research include: (1) What is the judge's decision in case number 0508/Pdt.G/2016/PA. Mtr concerning the settlement of disputes in murabahah financing contracts according to the theory of Islamic Economics Law? (2) How is the judge's decision in case number 0508/Pdt.G/2016/PA. Mtr concerning the settlement of disputes in murabahah financing contracts according to the principle of justice in Sharia Economic Law? When viewed from the method of data collection, this type of research includes the type of library research because the data collection techniques that the authors chose in this study is techniques of collecting data through the documentation method. In analyzing the data the author uses a comparative approach to compare the practice of banking contracts - which in this study are the problems of murabahah and musyarakah financing contracts - as stated in the decisions of the Mataram Religious Court judges in accordance with the contract theory regulated in sharia economic law.The results of this study are: (1) Procedure for settling a dispute case in murabahah and musyarakah contracts carried out by the of judges through their decision Number 0508/Pdt.G/2016/PA. Mtr along with the contents of the decision according to the author in accordance with the rules stipulated in Sharia Economic Law. That is because the dispute resolution carried out by the judges is carried out based on legal rules in Sharia Economic Law, namely the rules for resolving sharia economic disputes contained in Law Number 21 of 2008 concerning Islamic Banking Article 55, Law Number 48 Year 2009 concerning Judicial Power Article 16 paragraph 2, Supreme Court Regulation Number 2 of 2008 concerning Compilation of Sharia Economic Law Article 133, and DSN-MUI Fatwa Number 4 concerning Murabahah, Number 8 of 2000 concerning Musyarakah Financing, and Number 47 concerning Settlement of Murabahah Receivables for Customer Can't Pay. (2) Decision of the judges in Case Number 0508/Pdt.G/2016/PA. Mtr Concerning Settlement of Murabahah Financing Contract Disputes according to the author in accordance with the principle of justice in Sharia Economic Law.Â Keywords: Contract, Murabahah, Musyarakah, Law, Sharia Economy.Â